I.M. Pei : complete works - Jodidio, Philip; Strong, Janet Adams, 1951- (New York : Rizzoli ; Distributed to the U.S. trade by Random House, 2008)
When I. M. Pei was awarded the Pritzker Prize in 1983, the jury said he had "given this century some of its most beautiful interior spaces and exterior forms." I. M. Pei: Complete Works, the first and definitive survey of the master architect, attests to this statement by showcasing Pei's transcendent, sculptural forms in over fifty projects and more than 300 illustrations, culminating in the last works he is currently completing. Often working in a spare geometry with a palette of stone, concrete, glass, and steel, Pei--who began his career pioneering public housing projects in New York City--has taken his vision of modern architecture across the globe with commissions in locations as diverse as Quatar, China, Luxembourg, Japan, and Germany. Meanwhile, major projects such as the JFK Library in Boston and the East Building of the National Gallery of Art in Washington, D.C., have made him a household name in the United States.
Includes bibliographical references (p. 342-353) and index.
Keywords: Pei, I. M., -- 1917-; Architecture, Modern -- 20th century; Architecture, Modern -- 21st century